Analisis Pengaruh Temperatur Suhu dan Kecepatan Putar Screw Terhadap Hasil Filament 3D Printing Pada Mesin Filament Extruder Menggunakan Metode Taguchi - Triatna, Rajuwiraraja; Sateria, Angga; Husman, Husman (Jurnal Inovasi Teknologi Terapan, 2025)
The development of 3D printing technology has opened up great opportunities in various industries, especially in the manufacture of complex three-dimensional objects. However, the quality of the print results is greatly influenced by the physical and mechanical properties of the filament used. The filament production process, especially in filament extruder machines, requires extra attention to operational parameters such as extrusion temperature and screw rotation speed. Variations in these parameters significantly affect filament quality, such as tensile strength and thickness, which can decrease if not properly adjusted. This study aims to analyze the effect of extrusion temperature and screw rotation speed parameters on filament quality, and to determine the optimal settings using the Taguchi method. The results showed that screw rotation speed is the most significant faktor in determining filament diameter with a contribution of 73%. In addition, extrusion temperature contributes 17.6%. Through optimization using the Taguchi method, it is known that the optimal extrusion temperature is 250°C with a screw rotation speed of 5 RPM, producing filament with a diameter of 1.8 mm.